Digital Services and Social Stability: Evaluating the Impact from a Maqasidic Approach - Bendebka, Ramzi; Fettane, Amar; Shogar, Ibrahim Adam Ahmed (2021)
During the Covid-19 epidemic, there was an urgent need for many countries in the world to move as quickly as possible towards digital services such as e-government, e-learning, and e-commerce. The positive aspects of this transformation cannot be overlooked; however, other negative effects may result from the long and medium term of such an approach. For instance, do all governments can provide Internet access to serve the interests of their citizens. Therefore, this research will ask: what are the effects of the increasing trend towards digital services and how can they affect societal stability? How can these effects be dealt with from a Maqasidic approach? To answer these questions, the researcher used the inductive approach to collect information on the subject matter and related concepts, terms and opinions related to digital services and social stability. Also, the analytical approach will show the effects of digital services on social stability with a specific focus on Maqasid Shariah. Among the most prominent results of the research are that: quality of information accessibility, equality, social trust, social cohesion, and community engagement are the main aspects that can be affected by digital services. Therefore, moving towards digital services must be directed by Maqasid al-Shariah as a frame to maintain social stability and peace.